The Effects of Net Working Capital on Return on Assets in PT Perkebunan Nusantara III (Persero) Medan - Januri Januri (AIBPM Publisher, 2021)
This study deals to reveal whether net working as measured by cash turnover, accounts receivable turnover, inventory turnover has an effect on Return on Assets (ROA) at PT Perkebunan Nusantara III (Persero) Medan on period 2015-2019. This study used an associative approach and quantitative research then it used Kendall Tau correlation test as data analysis technique. The results showed that cash turnover has an effect on ROA, accounts receivable turnover has an effect on ROA, inventory turnover has no effect on ROA, while simultaneously cash turnover, receivable turnover, inventory turnover influenced ROA at PT Perkebunan Nusantara III (Persero) Medan on period 2015-2019.